Design and Implementation of Remote Monitoring and Control Service of Electric Vehicle Based on CoAP Protocol in IoV Networks - Xuan, Songai; Lee, Dongin; Lee, Hyeon-Cheol; Lee, Sang-Gyu; Hyeun Kim, Do (International Journal of Engineering and Technology, 2018)
Background/Objectives: Electric vehicles are cost-effective, environment friendly and its use is growing day-by-day in many developed countries.Â  To further enhance the performance of electric vehicle and user experience, we propose a remote monitoring service in mobile platform using CoAP protocol. And we design and implement of remote monitoring and control service of electric vehicle based on CoAP protocol in IoV networks.Methods/Statistical analysis: In this paper, we propose an electric vehicle remote monitoring system based on the CoAP protocol, which enables us to monitor and control the services of electric vehicles via mobile Phones. For analysis, we have used an electric vehicle emulator to conduct these experiments.Findings: We find it feasible and effective to use CoAP protocol for the communication between vehicle emulator and mobile application. We have successfully monitored and controlled the state of the vehicle emulator through mobile application using CoAP protocol. The following are the vehicle emulator states include engine state (start or stop), door state (lock/unlock), head lights state (turn on/off), interior light state ((turn on/off)), head lights status, audio state (turn on/off), alarm state (turn on/off), and the trunk state (lock/unlock).Improvements/Applications: For these experiments, we used electric vehicle emulator instead of real electric vehicles, and implement our design successfully. We have planned to optimize our design by using real electric vehicles instead of emulators in our future work.Â